Secure communication in Vehicular ad hoc network using modified ad hoc on demand distance vector - Abdulkader, Zaid A. (2018)
Vehicular ad hoc networks (VANETs) can potentially increase road safety dramatically by providing drivers with more time to adequately respond to dangerous situations. To safeguard VANETs from abuse, they need a security infrastructure to ensure security requirements like authentication, confidentiality, and availability. First threat is on VANET availability: The network has to always be available even if it undergoes attack. To do this, it must use alternative mechanisms while making sure that it does not affect its performance. A Blackhole attack is considered one of the most harmful and active attacks example on the availability of VANETs. Second threat is on confidentiality: Confidentiality ensures that the data is only accessible to the designated recipient and that other users cannot access the data. It therefore ensures that the data remains untouched until it is received by the designated recipient. Wormhole attack is the most sophisticated and hostile attack example against VANET confidentiality. Third threat is on authentication: Vehicles must only respond to messages that are sent by legitimate network members. Thus, authenticating the sender of a message is vital. One of the most especially dangerous attacks example on authority in VANET is referred to as the Sybil attack. These kind of threats can impact on the VANET’s applications like safety application and road congestion management application, so that, it will increase the road accidents. They can hide emergency massages like collision warning and traffic jam warning massages. This study suggests a framework that can be used for secure VANET communication in city scenario. In our framework we use Ad hoc On demand Distance Vector (AODV) because it is the most suitable routing protocol for VANET and the current routing protocols have mostly been designed for MANETs. AODV can be applied in VANETs because it is able to deal with continually evolving topology and high mobility speed of VANET. Since AODV has no security mechanisms, malicious nodes can perform many attacks just by not behaving according to the AODV rules, so that our framework can provide secure communication in VANET via modifying AODV. Our framework categorises the requirements for the VANET protection design via modifying AODV into three: Insure the Availability of VANET and its Services Algorithm (IAVSA), Protect Data Dissemination Algorithm (PDDA), and Secure Vehicles Authentication Algorithm (SVAA). The OMNET++ simulation program is used to justify the proposed algorithms. This is done based on the specific parameters such as (number of malicious nodes, number of normal nodes, and maximum speed). In instances when Blackhole and wormhole attacks take place in IAVSA and PDDA, a high detection rate that is close to 99% is observed. Furthermore, when a Sybil attack takes place, SVAA can identify 97% of the Sybil attacks. The simulation also illustrates that it had a high packet delivery ratio and low end-to-end delay.